A High-Throughput Photon Processing Technique for Range Extension of SPAD-Based LiDAR Receivers - Patanwala, Sarrah M.; Gyongy, Istvan; Mai, Hanning; Abmann, Andreas; Dutton, Neale A. W.; Rae, Bruce R.; Henderson, Robert K. (IEEE open journal of solid-state circuits, 2022)
There has recently been a keen interest in developing Light Detection and Ranging (LiDAR) systems using Single Photon Avalanche Diode (SPAD) sensors. This has led to a variety of implementations in pixel combining techniques and Time to Digital Converter (TDC) architectures for such sensors. This paper presents a comparison of these approaches and demonstrates a technique capable of extending the range of LiDAR systems with improved resilience to background conditions. A LiDAR system emulator using a reconfigurable SPAD array and FPGA interface is used to compare these different techniques. A Monte Carlo simulation model leveraging synthetic 3D data is presented to visualize the sensor performance on realistic automotive LiDAR scenes.